Association between anticholinergic drug burden with sarcopenia, anthropometric measurements, and comprehensive geriatric assessment parameters in older adults. (March 2022) - Bag Soytas, Rabia; Arman, Pinar; Suzan, Veysel; Emiroglu Gedik, Tugce; Unal, Damla; Suna Erdincler, Deniz; Doventas, Alper; Yavuzer, Hakan
Highlights: Older patients use multiple drugs due to their comorbidities. Most of these drugs have anticholinergic drug burden (ADB). ADB affects functional disability, but its effect on sarcopenia has not been known. This is the first study to investigate the effect of ADB on sarcopenia. ADB may be a risk factor for sarcopenia by decreasing handgrip strength. Abstract: Background: Older patients use multiple drugs due to their comorbidities and most of these drugs have anticholinergic drug burden (ADB). We aimed to investigate the association between ADB and sarcopenia, anthropometric measurements, and comprehensive geriatric assessment (CGA) parameters in older adults. Methods: Patients ≥65 years who applied to geriatrics outpatient clinic between January 2019-March 2020 were included. Patients with cognitive dysfunction were excluded. CGA tests were conducted on patients. Handgrip strength (HGS), bioelectrical impedance analysis (BIA), and a 6-meter walking test were used for sarcopenia definition. The Anticholinergic Cognitive Burden (ACB) scale was used to calculate the ADB. Results: Totally 256 patients (women/men:180/76) were included. The mean age was 82±6.8. Two groups were created as without ADB (n=116) and with ADB (n=140). Sarcopenia was higher in the ADB group (p=0.04). In women and men as ADB increased HGS decreased (respectively; p=0.023 r=-0.170, p=0.031 r=-0.248) and Basic Activities of Daily Living (BADL) test score increased (respectively; p= <0.001 r= 0.292, p=0.04 r= 0.244). In the linear regression (LR) analysis age and BADL test score had significant association with ADB in women (respectively; p=0.001, p=0.023). Conclusion: The finding that sarcopenia is higher in the patients with ADB and HGS decreases as ADB increases, suggesting that ADB may be a risk factor for sarcopenia by decreasing HGS. Also, it has been determined that, especially in older women, as ADB increases, the dependence on basic daily living activities increases.